Characterization of novel oil palm defense-related transcription factors during biotrophic and necrotrophic infection phases of Ganoderma boninense - Mohd Sakeh, Nurshafika (2020)
Basal stem rot (BSR) disease, caused by Ganoderma boninense has been pinpointed to be one of the major factors that contribute to the decline in yield of oil palm. Hemibiotroph pathogen such as G. boninense manipulates the host defense mechanisms to strategically infect host plant by switching from biotrophic to necrotrophic phase. Recognizing the early infection phase of G. boninense by identifying phase-specific oil palm transcription factors (TFs) may offer opportunities to tackle or attenuate the progress of infection. The fragmentary information on molecular interactions between plant and hemibiotroph should be explicated to identify the key molecular mechanisms of pathogenesis and plant immunity. Thus, this study is an attempt to recognize specific TFs as ‘key’ biomarkers in identifying oil palm defense mechanisms during biotrophic and necrotrophic infection phases of G. boninense. Artificial infection of G. boninense on oil palm was performed by using Ganoderma-inoculated rubber wood blocks (RWBs) and bare RWBs serves as mock-treatment presenting abiotic stress. In order to identify oil palm defense response during early interaction with G. boninense, transcriptomic analysis of root tissues at different time points of 3, 7 and 11 days post inoculation (d.p.i) was carried out. High-throughput RNA-seq data analysis has revealed two distinguishable expression profiles of oil palm genes that formed the basis for deducing biotrophic phase at early interaction (3 d.p.i) which switched to initiation of necrotrophic phase at later stage (11 d.p.i) of infection. Based on the findings, the present study focused on identifying differentially expressed genes (DEGs) encoding TFs from the generated RNA-seq data. A total of 106 upregulated and 108 downregulated DEGs of TFs were identified. There are four established defense-related pathways that have been presented whereby reported genes involved in cell wall modification, reactive oxygen species (ROS)-mediated signaling, programmed cell death (PCD) and plant innate immunity were differentially expressed. The genes were found to be either upregulated or downregulated during the two distinct infection phases. Multiplex semi-quantitative RT-PCR was conducted to screen for defense-related TFs independent of abiotic stress. Normalized band intensity of Ganoderma-treated (GT) samples were compared to the mock-treated (MT) samples to estimate the mRNA expression level between groups. The expression patterns of eight candidate TFs genes including EgJUB1, EgERF113, EgTCP15, EgNAC29, EgEIN3, EgMYC2, EgNAC83 and EgMYB122 were further quantified via quantitative Real-Time PCR (qPCR). Both EgJUB1 and EgERF113 were found to be specifically upregulated under biotic stress at all time points. The findings discovered upregulation of EgJUB1 during biotrophic phase while EgERF113 demonstrated prominent upregulation as oil palm switches to defense against necrotrophic phase. Characterization of EgJUB1 and EgERF113 was performed via in vivo Yeast One-Hybrid (Y1H) assay and in vitro electrophoretic mobility shift assay (EMSA). JUB1 has been reported to bind to NAC binding site (NACBS) motif during abiotic stress. The present study is the first report on the binding activity of EgJUB1 to secondary wall NAC binding element 1 (SNBE1) which was present in the promoter region of EgHSFC-2b having similar expression profile as EgJUB1. SNBE1 motifs with single nucleotide change at either 5th or 18th position have been found in the promoter regions of a few TFs that co-expressed with EgJUB1, including EgHSFB-4b and EgGAMYB X2. Meanwhile EgERF113 binds to GCC-box and DRE/CRT motifs promoting plasticity in upregulating downstream defense-related genes against G. boninense attack. Sequence analysis revealed the presence of NAC DNA binding domain (DBD) in EgJUB1. Amino acid change from phenylalanine (F) to tryptophan (W) at 14th position of EgERF113 DBD proved the binding specificity to both GCC-box and DRE/CRT motifs. Prolonged treatment revealed oil palm seedlings succumbing to the G. boninense infection. Mature basidiomata of G. boninense was observed at 24 weeks post inoculation (w.p.i) and the infection culminated in plant death. Overall, our findings propose EgJUB1 and EgERF113 as key TFs in orchestrating the oil palm defense mechanisms during biotrophic and necrotrophic infection phases of hemibiotrophic G. boninense, respectively.